2013
DOI: 10.1177/193758671300600306
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Perceptions of a Changing Hospital Environment

Abstract: Healing environments, organizational transformation, patient-centered care, pediatric, satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 38 publications
0
21
0
1
Order By: Relevance
“…However, important issues that require further research include concerns about potential additional workload, 4 stress 79 and risks to staff; 30,77,80,81,85 less patient surveillance; 11,37,38 and patients feeling isolated or alienated. 38,68,69 There is limited evidence about the costs and economic outcomes of higher proportions of single room accommodation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, important issues that require further research include concerns about potential additional workload, 4 stress 79 and risks to staff; 30,77,80,81,85 less patient surveillance; 11,37,38 and patients feeling isolated or alienated. 38,68,69 There is limited evidence about the costs and economic outcomes of higher proportions of single room accommodation.…”
Section: Discussionmentioning
confidence: 99%
“…A US study using comparative design to investigate how clinicians perceive, evaluate and adjust to a new hospital environment found the single-patient room model increased the workload of many clinicians and their stress had increased after 15 months. 77 The study showed that employees with 3 or more years of service had significantly higher stress than others, suggesting that staff with established work patterns may find it more difficult to adjust to new hospital designs. Staff stress could be greater if they feel less able to monitor patients, have less time for direct care or are less visible to patients.…”
Section: Introductionmentioning
confidence: 96%
“…, Verderber & Todd , Maguire et al . ). However, as Verderber and Todd () point out, the prioritisation of single rooms in the USA has been associated, predominantly, with private healthcare where single‐family rooms are seen as a mark of progressiveness and a marketable asset to potential users.…”
Section: Introductionmentioning
confidence: 97%
“…Spatial aspects are particularly pertinent given the trend, over recent years, for an increase in the number of single rooms, sometimes referred to as single-family or private rooms, and concomitant decrease in semi-private, or shared rooms (or bays) within paediatric hospitals internationally. 1 This change, initiated within the United States (US), has been justified in relation to claims for improved ambient qualities (including better light, reductions in environmental noise), enhanced infection control and assumed consumer preference (Kotzer et al 2011, Stevens et al 2012, Verderber & Todd 2012, Maguire et al 2013. However, as Verderber and Todd (2012) point out, the prioritisation of single rooms in the USA has been associated, predominantly, with private healthcare where single-family rooms are seen as a mark of progressiveness and a marketable asset to potential users.…”
Section: Introductionmentioning
confidence: 99%
“…As such, a greater proportion of single rooms are often incorporated into the design of new ICUs. There is, however, less known about the impact of single room environments on other workplace issues (Maguire et al, 2013) such as learning in the workplace (Walsh et al, 2006).…”
mentioning
confidence: 99%